Consumption behavior of eco-friendly products and applications of ICT innovation. (10th March 2021) - Chen, Sihua; Qiu, Han; Xiao, Hua; He, Wei; Mou, Jian; Siponen, Mikko
Abstract: The purchase of eco-friendly products is encouraged by the governments due to its contributions to the sustainable development of the environment. It is therefore important to examine factors influencing the purchase of eco-friendly products. Based on the attitude-behavior-context (ABC) theory, this paper constructs a conceptual model, which explores how a consumer's perceived effectiveness affects individuals' purchase of eco-friendly products. In details, this paper attempts to examine the mediating role of consumption attitude of eco-friendly products, as well as the moderating effect of applications of information and communication technologies (ICT) innovation. Moreover, by building a Hidden Markov Model (HMM), this paper further tests the conceptual model. More importantly, based on the HMM, the consumption probabilities of eco-friendly products of different perceived effectiveness under different applications of ICT innovation are computed. Furthermore, based on a dynamic time series, the consumption transition probability of eco-friendly products is further calculated. In addition, this paper explains and calculates the concepts continuity, dependence and inertia in consumption of eco-friendly products. Based on it, the algorithm is used to forecast the consumption behavior of the real environment to verify the reliability of the HMM and the accuracy of probability calculation. This paper contributes the extension of the existing studies and the provision of management implications and guidance for the consumption practice of eco-friendly products.